2018
DOI: 10.1002/2017jd027903
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Assessment of Global Surface Net Radiation Products and Uncertainty Analysis

Abstract: Earth surface net radiation (Rn) characterizes the surface radiation budget and plays a critical role in ecological, biogeochemical, and hydrological processes. The Rn products from remote sensing and reanalysis have not been validated comprehensively. In this study, four Rn products (Clouds and the Earth's Radiant Energy System [CERES], ERA‐Interim, Modern‐Era Retrospective analysis for Research and Applications version 2, and Japanese 55‐year Reanalysis) were validated using global ground measurements on mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 61 publications
2
41
0
Order By: Relevance
“…Our previous study also suggests that CERES EBAF R s retrievals have 9.9 W/m 2 mean absolute biases comparing with BSRN sites data (Feng & Wang, ). Existing study suggest that changing the MODIS AOD from Collections 4 to 5 resulted in the discontinuity in the CERES EBAF global land R s in 2006 (Jia et al, ). Moreover, satellite AOD retrievals are only available under cloud‐free conditions, which cannot fully represent AOD trend in the all‐weather situation.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study also suggests that CERES EBAF R s retrievals have 9.9 W/m 2 mean absolute biases comparing with BSRN sites data (Feng & Wang, ). Existing study suggest that changing the MODIS AOD from Collections 4 to 5 resulted in the discontinuity in the CERES EBAF global land R s in 2006 (Jia et al, ). Moreover, satellite AOD retrievals are only available under cloud‐free conditions, which cannot fully represent AOD trend in the all‐weather situation.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of reviewed studies (61) facilitated more than one validation method. Hereby, a variety of studies showed, in particular, the combination of an intercomparison of products with a comparison to reference data [9,21,35,48,53,54,57,59,84,97,[120][121][122][123][124]129,133,135,139,[141][142][143][144][145]. This dual approach can provide an indication of general remote sensing performance for a particular research area or, on the other hand, illustrate improvements of novel methods in relation to existing products [35,71,136].…”
Section: Combination Of Methodsmentioning
confidence: 97%
“…Along with similar remote sensing products for this type of validation, products in the form of model outcomes featuring the same target variable are also considered [120][121][122]. For instance, Albergel et al [123] intercompared a fused radar soil moisture product with two reanalysis datasets.…”
Section: Validation By Intercomparison Of Related Productsmentioning
confidence: 99%
“…Overall, MERRA-2 provides more self-consistent meteorological data than its previous versions at large scale [68,99]. Although some validations of the recent MERRA-2 surface and atmospheric reanalysis have been published [100,101], there is a lack of comprehensive assessment at regional scales.…”
Section: The Sebal Sensitivity To Meteorological Inputsmentioning
confidence: 99%